Desconstrução da alfaiataria: um estudo para proposição de design de superfície por meio da técnica recorte - Marques, Raysa Zacarias (2017)
For years, the tailoring that we now call classical and traditional was highly desired by men in general. More recently, driven by the speed of information, the quick changes of costumes and lifestyle, have imposed on the current man and consequently on the tailoring, the need to develop novelties that would satisfy the new desires that emerged from these transformations. In observing this current behavior, with regard to the new needs of contemporary man, bibliographical and field research were carried out to better understand this market niche. In this sense, the objective of this work is to develop a collection for the male audience, from 25 to 35 years old, having as a differential the cut as Surface Design in the pieces of tailoring.